2022
DOI: 10.3390/molecules27238155
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Isolation and Data Independent Acquisition Mass Spectrometry (DIA-MS) of Urinary Extracellular Vesicles to Improve Prostate Cancer Diagnosis

Abstract: Proteomic profiling of extracellular vesicles (EVs) represents a promising approach for early detection and therapeutic monitoring of diseases such as cancer. The focus of this study was to apply robust EV isolation and subsequent data-independent acquisition mass spectrometry (DIA-MS) for urinary EV proteomics of prostate cancer and prostate inflammation patients. Urinary EVs were isolated by functionalized magnetic beads through chemical affinity on an automatic station, and EV proteins were analyzed by inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…46 Zhang et al, performed proteomic analysis of urinary EVs from prostate cancer and prostate inflammation patients using a DIA-constructed spectral library and identified 18 EV proteins that were significantly differentially expressed. 47 Halal et al, also applied library-based DIA to profile circulating EVs from glioma patients and healthy controls, achieving a coverage of 4054 proteins. 48 Chutipongtanate and Greis also previously reported the application of a curated library-based DIA for urinary EVs, detecting 888 proteins.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Zhang et al, performed proteomic analysis of urinary EVs from prostate cancer and prostate inflammation patients using a DIA-constructed spectral library and identified 18 EV proteins that were significantly differentially expressed. 47 Halal et al, also applied library-based DIA to profile circulating EVs from glioma patients and healthy controls, achieving a coverage of 4054 proteins. 48 Chutipongtanate and Greis also previously reported the application of a curated library-based DIA for urinary EVs, detecting 888 proteins.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Zheng et al, demonstrated the potential of DIA-MS to validate circulating extracellular vesicles biomarkers in colorectal cancer patient samples . Zhang et al, performed proteomic analysis of urinary EVs from prostate cancer and prostate inflammation patients using a DIA-constructed spectral library and identified 18 EV proteins that were significantly differentially expressed . Halal et al, also applied library-based DIA to profile circulating EVs from glioma patients and healthy controls, achieving a coverage of 4054 proteins .…”
Section: Resultsmentioning
confidence: 99%
“…Gamma-glutamyltransferase 1 was shown to be expressed at higher levels in urinary sEVs and tissues of PCa patients [ 145 ]. Zhang reported that urine sEV protein markers (SERPINA3, LRG1, and SCGB3A1) were higher in PCa patients (n = 20) than in healthy controls (n = 20), with SERPINA3 showing the highest correlation in distinguishing patients from healthy individuals [ 147 ]. Additionally, FABP5 was found to be not only higher in the PCa group compared with the control group, but also significantly correlated with Gleason grading in urinary sEVs [ 146 ].…”
Section: Sev Proteins As Diagnostic or Prognostic Biomarkers In Pca L...mentioning
confidence: 99%
“…In prostate cancer, the exosomes from different compartments were studied [145]. For example, the potential of urinary EVs [146] and plasma-derived exosomes [147] was explored. In a recent article, the authors did the proteomic analysis of EVs isolated from the blood sera of prostate cancer patients, healthy donors, patients with hypertrophic disease, and post-prostatectomy disease-free cases.…”
Section: The Biomarker Potential Of Evs-derived Integrins In Prostate...mentioning
confidence: 99%